POSTPRANDIAL HYPOGLYCEMIA: A RARE PRESENTATION OF AN INSULINOMA - Hee, Nicholas Ken Yoong; Lim, Quan Hziung; Ooi, Ying Guat; Sarvanandan, Tharsini; Ratnasingam, Jeyakantha; Paramasivam, Sharmila; Lim, Lee Ling; Vethakkan, Shireene Ratna (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Insulinomas typically present with fasting hypoglycemia, owing to the autonomous secretion of insulin from this neuroendocrine tumor. A presenting complaint of postprandial hypoglycemia in a patient with insulinoma is rare, with a slight male predominance. CASE A 66-year-old male with chronic kidney disease (stage G4A2) and interstitial lung disease presented to our centre with two episodes of post-prandial hypoglycaemia, resulting in loss of consciousness. The first occurred 2 hours after breakfast; the second, a month later, occurred 3 hours after breaking fast following a 14-hour fast during Ramadan. During the episode of postprandial hypoglycaemia, he fulfilled Whipple’s triad with venous blood glucose 1.0 mmol/L, insulin 42.9 m IU/L and C-peptide 21.1 ng/mL. A 72-hour prolonged fast conducted and terminated at 42 hours revealed a nadir glucose of 2.5 mmol/L but low insulin of 2.0 m IU/L and elevated C-peptide 2.2 ng/mL. Peak ketone was 2.4 mmol/L, consistent with endogenous hyperinsulinism. A mixed meal test triggered hypoglycaemia of 2.3 mmol/L at 210 minutes, with insulin 25.5 m IU/L and C-peptide 17.2 ng/mL. Sulphonylurea screen and insulin autoantibodies were negative. Both transabdominal and endoscopic ultrasounds revealed a 3.3 x 3.3 cm hyperechoic head of pancreas mass. A fine needle biopsy during EUS was done and immunohistochemistry of the specimen was positive for insulin and synaptophysin, consistent with insulinoma. The patient was started on diazoxide and put on a continuous glucose monitoring system. This also showed low glucose readings predominantly after meals. Unfortunately, he developed severe pneumonia and passed away prior to functional imaging and definitive surgery. CONCLUSION Kidney disease does elevate C-peptide levels, which may confound the evaluation of hypoglycemia.2 Clinicians should have a high index of suspicion for insulinoma, even in patients with a history of predominantly postprandial hypoglycaemia when confronted with high C-peptide levels in both fasting and postprandial states.